2014
DOI: 10.4041/kjod.2014.44.5.254
|View full text |Cite
|
Sign up to set email alerts
|

The relation between idiopathic scoliosis and the frontal and lateral facial form

Abstract: ObjectiveThe purpose of this study was to evaluate the relation between idiopathic scoliosis and facial deformity in the horizontal, vertical, and anteroposterior planes.MethodsA total of 123 female patients aged 14 years or older, who visited the Spine Clinic at the Department of Orthopedics, Korea University Guro Hospital for treatment of idiopathic scoliosis, were enrolled. Whole-spine anteroposterior and lateral radiographs were taken with the patient in a naturally erect position, and frontal and lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…This finding is correlated with a previous report where the horizontal skeletal pattern (ANB angle) parameters in the lateral cephalometric measurements showed no significant difference among idiopathic scoliosis in female patients between 14 and 28.5 years old. 24 These findings were related to previous reports for the postural compensatory mechanism, which might have minimised the effects of one area due to jaw position and body posture. Cervical spine measurements were significantly correlated, rejecting the association between trunk and back.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is correlated with a previous report where the horizontal skeletal pattern (ANB angle) parameters in the lateral cephalometric measurements showed no significant difference among idiopathic scoliosis in female patients between 14 and 28.5 years old. 24 These findings were related to previous reports for the postural compensatory mechanism, which might have minimised the effects of one area due to jaw position and body posture. Cervical spine measurements were significantly correlated, rejecting the association between trunk and back.…”
Section: Discussionsupporting
confidence: 87%
“… 22 However, hypotheses describing the correlations between scoliosis and occlusion have varied in recent decades. 10 , 23 - 26 This correlation was assumed to be based on the anatomic and functional connections between the stomatognathic complex and the cervical vertebra. An anatomic connection refers to the muscular and ligament attachments between the craniofacial complex and the cervical vertebra, while functional connections among the cranium, mandible, and cervical vertebra are adjusted by visual balance and a gravity effect.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of body posture is a special investigation parameter nowadays since the goal of orthodontic treatment includes achieving good stability in addition to aesthetics and function. Even though Algadhir et al [12] suggested that jaw positions should be considered in treatment and rehabilitation planning for healthy patients with postural instability, a different study reported postural parameters found not to be accurate in the juvenile population with unilateral posterior crossbite [23].…”
Section: Discussionmentioning
confidence: 99%